Evaluation of the quality of the reporting of phase II clinical trials in oncology: A systematic review. (May 2018) - Rivoirard, Romain; Langrand-Escure, Julien; Oriol, Mathieu; Tinquaut, Fabien; Chauvin, Franck; Rancoule, Chloé; Magné, Nicolas; Bourmaud, Aurélie
Abstract: Objective: To describe the current state of knowledge concerning the quality of reporting in phase II clinical trials in oncology and to describe the various methods published allowing this quality evaluation. Methods: databases including MEDLINE and COCHRANE were searched. Reviews and meta-analyses analyzing the quality of the reporting of phase II trials in oncology were included. Descriptive analysis of the results was performed. Results: Thirteen publications were retained. Only 2 publications adopted a systematic approach of evaluation of the quality of reporting by overall scores. The Key Methodological Score (KMS), proposed by Grellety et al., gathering 3 items, seemed adapted for such an evaluation. A score of 3/3 was found in 16.1% of the 156 phase II trials analysed by this score. The other reviews used a qualitative analysis to evaluate the reporting, via an analysis of a single criterion, generally the statistical plan of the study. This item was considered as having been correctly reported in less than 50% of the analysed articles. Conclusion: The quality of reporting in phase II trials in oncology is a field that has been investigated very little (13 publications). When it is studied, the estimated level of quality is not satisfactory, whatever the method employed. The use of an overall score of evaluation is a path which should be pursued, in order to get reliable results. It also seems necessary to propose strong recommendations, which would create a consensus for the methodology and the reporting of these studies.